Coping, Resilience, and Perceived Stress in Individuals with Internet Gaming Disorder in Taiwan - Lin, Pai-Cheng (Int J Environ Res Public Health, 2021)
Aim: Gaming escapism is an essential factor for developing internet gaming disorder (IGD). We evaluated coping strategies, resilience, stress, and depression in individuals with IGD. Methods: We included 69 participants with IGD and 138 controls (69 regular gamers and other non-gamers) in Taiwan. The self-reported coping strategies, coping stress with gaming, resilience, perceived stress, and depression were assessed. Results: Participants with IGD had higher dysfunctional coping, coping stress by gaming, perceived stress, and depression, as well as lower problem-focused coping and resilience. Regression analysis revealed that coping by gaming was associated with dysfunctional coping mechanisms, particularly venting and self-distraction. Compared with participants with adequate resilience, those with lower resilience had higher perceived stress, depression, and coping by gaming, and lower problem-focused and emotion-focused coping. Dysfunctional coping and coping by gaming were associated with perceived stress and depression in both IGD and control groups. Problem-focused coping was negatively associated with perceived stress and depression in controls. Conclusion: Individuals with IGD had higher perceived stress and depression, as they were more likely to cope with stress by dysfunctional coping and gaming and less likely to try problem-focused coping, particularly those with lower resilience. Interventions for IGD should promote problem-focused coping, such as active coping and planning strategies, particularly among those with lower resilience.